Ripple-AT Study: A Multicenter and Randomized Study Comparing 3D Mapping Techniques During Atrial Tachycardia Ablations. (August 2019) - Luther, Vishal; Agarwal, Sharad; Chow, Anthony; Koa-Wing, Michael; Cortez-Dias, Nuno; Carpinteiro, Luís; de Sousa, João; Balasubramaniam, Richard; Farwell, David; Jamil-Copley, Shahnaz; Srinivasan, Neil; Abbas, Hakam; et al.
Abstract : Background: Ripple mapping (RM) is an alternative approach to activation mapping of atrial tachycardia (AT) that avoids electrogram annotation. We tested whether RM is superior to conventional annotation based local activation time (LAT) mapping for AT diagnosis in a randomized and multicenter study. Methods: Patients with AT were randomized to either RM or LAT mapping using the CARTO3v4 CONFIDENSE system. Operators determined the diagnosis using the assigned 3D mapping arm alone, before being permitted a single confirmatory entrainment manuever if needed. A planned ablation lesion set was defined. The primary end point was AT termination with delivery of the planned ablation lesion set. The inability to terminate AT with this first lesion set, the use of more than one entrainment manuever, or the need to crossover to the other mapping arm was defined as failure to achieve the primary end point. Results: One hundred five patients from 7 centers were recruited with 22 patients excluded due to premature AT termination, noninducibility or left atrial appendage thrombus. Eighty-three patients (pts; RM=42, LAT=41) completed mapping and ablation within the 2 groups of similar characteristics (RM versus LAT: prior ablation or cardiac surgery n=35 [83%] versus n=35 [85%], P =0.80). The primary end point occurred in 38/42 pts (90%) in the RM group and 29/41pts (71%) in the LAT group ( P =0.045). This was achieved without any entrainment in 31/42 pts (74%) with RM and 18/41 pts (44%) with LAT ( P =0.01). Of those patients who failed to achieve the primary end point, AT termination was achieved in 9/12 pts (75%) in the LAT group following crossover to RM with entrainment, but 0/4 pts (0%) in the RM group crossing over to LAT mapping with entrainment ( P =0.04). Conclusions: RM is superior to LAT mapping on the CARTO3v4 CONFIDENSE system in guiding ablation to terminate AT with the first lesion set and with reduced entrainment to assist diagnosis. Clinical Trials Registration: https://www.clinicaltrials.gov . Unique identifier: NCT02451995. Abstract : Supplemental Digital Content is available in the text.